Upregulation of Cardiac IL-10 and Downregulation of IFN-γ in Balb/c IL-4−/− in Acute Chagasic Myocarditis due to Colombian Strain of Trypanosoma cruzi - Marcos Vinicius da Silva; Vera Lúcia de Almeida; Wendyson Duarte de Oliveira; Natália Carasek Matos Cascudo; Pollyana Guimarães de Oliveira; Crislaine Aparecida da Silva; Aline Cristina Souza da Silva; Maria Luíza Gonçalves dos Reis Monteiro; Rosana Rosa Miranda Correa; Milton Adriano Pelli Oliveira; Ruy de Sousa Lino-Júnior; Mara Rúbia Nunes Celes; et al. (Mediators of Inflammation)
Inflammatory response in Chagas disease is related to parasite and host factors. However, immune system regulation has not been fully elucidated. Thus, this study is aimed at evaluating IL-4 influence on acute phase of Trypanosoma cruzi experimental infection through dosage of cytokine levels in cardiac homogenate of infected Balb/c WT and Balb/c IL-4−/− as well as its histopathological repercussions. For such purpose, mice were divided into two groups: an infected group with 100 forms of the Colombian strain and an uninfected group. After 21 days of infection, animals were euthanized and the blood, spleen, and heart were collected. The spleen was used to culture splenic cells in 48 h. Subsequently, cytokines TNF-α, IL-12p70, IL-10, IFN-γ, and IL-17 were measured in the blood, culture supernatant, and heart apex by ELISA. The base of the heart was used for histopathological analysis. From these analysis, infected Balb/c IL-4−/− mice showed milder inflammatory infiltrate compared to Balb/c WT, but without changes in nest density and collagen deposition. IL-4 absence culminated in lower cardiac tissue IFN-γ production, although it did not affect TNF-α expression in situ. It also decreased TNF-α systemic production and increased IL-10, both systemically and in situ. In addition, IL-4 absence did not influence IL-17 expression. Splenocytes of IL-4-deficient mice produced higher amounts of IFN-γ, TNF-α, and IL-17 and lower amounts of IL-10. Thus, IL-4 absence in acute phase of experimental infection with T. cruzi Colombian strain reduces myocarditis due to lower IFN-γ production and greater IL-10 production in situ and this pattern is not influenced by splenocyte general repertoire.